The Utility of Animal Models in the Preclinical Study of Interventions to Prevent Human Coronary Artery Restenosis: Analysis and Recommendations - Johnson, G. J.; Griggs, T. R.; Badimon, L. (Thrombosis and Haemostasis, 1999)
Small animal models have several advantageous characteristics, but those used in preclinical restenosis research have lacked efficacy in predicting the success of interventions to inhibit restenosis in humans.Large animal models have been more successful than small animal models in predicting efficacy of interventions to inhibit restenosis in humans, but the results of studies carried out with these models have not been uniformly predictive.Confirmation of the results of small animal studies in large animals has not always yielded information predictive of success in humans; however, the absence of such confirmation has had strong negative predictive value.Small animal models used for evaluation of interventions to inhibit luminal narrowing following arterial instrumentation have failed to closely simulate human atherosclerosis and the stenotic lesions subjected to instrumentation in humans.Transgenic, atherosclerotic animals hold promise for the development of more useful small animal models to study mechanisms of the response of diseased arteries to angioplasty and stents.The pig has been the most useful large animal to study stenosis/ restenosis, but more information is needed to overcome the limitations of this model.